TEACHING SPEAKING THROUGH RETELLING NARRATIVE TEXT - Rani, A.; Supardi, Iwan; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Â ABSTRACTThis thesis is a study Drilling Vocabulary by Using Jumbled Letter to the Class VII Students of SMP Negeri 02 Semparuk, Sambas Regency, in Academic Year 2013. The purpose of the research is to find out how effective the scrambled letters is minimize the difficultes in vocabulary accurately to Class VII C Students of SMP Negeri 02 Semparuk, Sambas Regency, in Academic Year 2013/2014.The method of this research is class room action research method. The sample of his research is Class VII C Students of SMP Negeri 02 Semparuk, Sambas Regency, in Academnic Year 2013/2014 wich consisted of 30 students. The data of this research were collected by measurement technique. The measurement technique was employed to measure the studentsâ€™ achievement and it is done trough written tes.The findings of this research analyzed by the result of the studentsâ€™ scoreÂ  in the first cycle and second cycle. The result of the research was the total score of first cycle = 136 with mean score (4.86) it is qualified â€œaverage to goodâ€. The mean score of posttest (7.25) is bigger than the mean score of pretest (4.86), with score 2.39. the conclusion of this research was the drilling vocabulary through jumbled letters was effective to be applied in improving the studentsâ€™ achievement in spelling.Â Key Words: Teaching Speaking, Through Retelling, Narrative Text